2019
DOI: 10.1021/acsabm.8b00366
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Silver Nanoparticles Contained in Photoresponsive Nanogels

Abstract: Smart nanomaterials can selectively respond to a stimulus and consequently be activated in specific conditions, as a result of their interaction with electromagnetic radiation, biomolecules, or pH change. These nanomaterials are produced through distinct routes and can be used in artificial skin, drug delivery, and other biomedical applications. Here, we report on the fabrication of an antibacterial nanogel formed by aniline- and chitosan-containing silver nanoparticles (AgNp’s), with an average size of 78 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Besides, a 405 nm light-responsive nanogel (AgNP-nanogel) was synthesized by Ballesteros and co-workers. Silver ions were chelated in the aniline–chitosan (CS) nanogel structure . The electron migration on the silver surface was triggered by the 405 nm light to destroy the hydrogen bond, thereby promoting the release of silver ions.…”
Section: Stimuli-responsive Release Of Silver Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a 405 nm light-responsive nanogel (AgNP-nanogel) was synthesized by Ballesteros and co-workers. Silver ions were chelated in the aniline–chitosan (CS) nanogel structure . The electron migration on the silver surface was triggered by the 405 nm light to destroy the hydrogen bond, thereby promoting the release of silver ions.…”
Section: Stimuli-responsive Release Of Silver Ionsmentioning
confidence: 99%
“…Silver ions were chelated in the aniline−chitosan (CS) nanogel structure. 70 The electron migration on the silver surface was triggered by the 405 nm light to destroy the hydrogen bond, thereby promoting the release of silver ions. What's more, the low pH in a bacteria-infected environment enabled protonation of the amino groups on the CS molecule, which further increased the size of the AgNP-nanogel.…”
Section: Stimuli-responsive Release Of Silver Ionsmentioning
confidence: 99%
“…Ballesteros and colleagues demonstrated that the irradiation of a nanogel at 405 nm induces the excitation of Ag NPs and thus the rupture of cross-linking, leading to its release over time. In this context, the kinetics of Ag NP release under irradiation with a 405 nm diode LED was investigated in Gram-negative Escherichia coli [77].…”
Section: Antibiotic Nanoparticlesmentioning
confidence: 99%
“…Nanogels have been widely explored as cargo carriers. The release of cargo from nanogels can be triggered with different stimuli, including redox potential [460,461], pH changes [462,463], salt concentration [464], US [29], temperature [465], or light [466][467][468]. Also, it is possible to render nanogels responsive to specific stimuli, such as magnetic fields [469], by decorating nanogels with magnetic NPs.…”
Section: Nanogelsmentioning
confidence: 99%